Canine dental microwear and light stable isotopic analyses of some South African holocene populations - Manning, Lee (Department of Archaeology, 2025)
This thesis uses light stable isotope analyses as the basis against which to evaluate the efficacy of canine dental microwear in distinguishing different diets between some Holocene populations in southern Africa. It has been recognised for some time that the use of stable isotopes as the basis for dental microwear evaluations may be a valuable method for determining dietary activities. These methods are used together for the first time here. Three southern African Holocene populations representative of different dietary regimes were sampled for both carbon apatite and canine microwear. The information gleaned from carbon apatite values was supplemented by existing collagen information. General dietary trends are discernable between the three populations based on isotopic analyses. Coastal hunter-gatherer populations from Matjes River and Oakhurst subsisted largely on a diet of marine foods, supplemented by C3 or C4 terrestrial resources. K2 agriculturalists indicated diets based largely on the exploitation of domesticated stock supplemented by wild hunted/gathered/snared foods. Isotopic ratios for inland hunter-gatherers vary depending on geographical location, but largely reflect a diet based on the resources available from the biome of habitation. Two Harrismith burials, thought to be hunter-gatherers, may indicate some contact with sedentary populations. These dietary trends are not borne out by canine microwear analyses. Canine microwear indicates statistically significant differences only in the concentration of features. These differences are however subject to groupings and probability limits and are therefore not regarded as viable dietary indicators. Isotopic results for this study substantiate those from previous research in recognising dietary patterns associated with particular Holocene populations in southern Africa. However the analysis of canine dental microwear in human populations is not sensitive enough to detect dietary differences.